2019
DOI: 10.1007/s40264-019-00845-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Switching Originator and Biosimilar Epoetins in Patients with Chronic Kidney Disease in a Large-Scale Italian Cohort Study

Abstract: IntroductionReal-world data on the comparative effectiveness and safety of switching among different epoetins (including originators and biosimilars) are limited. In light of current debate about interchangeability, prescribers, some patient groups and decision makers are calling for additional post-marketing evidence on the clinical effects of switching between originator and biosimilar epoetins in chronic kidney disease (CKD) patients.ObjectiveThe objective of this study was to evaluate the effectiveness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
(20 reference statements)
0
16
0
2
Order By: Relevance
“…Despite the proven comparability of the efficacy and safety of biosimilar to the originator medicine and the great opportunity for cost saving, the acceptance of biosimilar agents among the medical community remains limited in some countries and therapeutic areas. 6 There are several cited reasons that could explain the lack of enthusiasm toward biosimilars, including the lack of provider confidence, uncertainty about substitution, and a lack of patient awareness and education. 12 In Kazakhstan, bESA become available in 2017, after which a few dialysis centers switched their patients to the newly introduced alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the proven comparability of the efficacy and safety of biosimilar to the originator medicine and the great opportunity for cost saving, the acceptance of biosimilar agents among the medical community remains limited in some countries and therapeutic areas. 6 There are several cited reasons that could explain the lack of enthusiasm toward biosimilars, including the lack of provider confidence, uncertainty about substitution, and a lack of patient awareness and education. 12 In Kazakhstan, bESA become available in 2017, after which a few dialysis centers switched their patients to the newly introduced alternative.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition to being a cost saving phenomenon, switching to biosimlars is something to be considered as a medical issue, particularly if it could occur with other medicines as well. 6 Since the year 2017, biosimilar ESA (bESA) have become available in Kazakhstani trade. Due to their lower prices compared to originator (rESA), a few of the country's dialysis centers switched their patients to bESA.…”
mentioning
confidence: 99%
“…Despite the proven comparability of the efficacy and safety of biosimilar to the originator medicine and the great opportunity for cost saving, the acceptance of biosimilar agents among the medical community remains limited in some countries and therapeutic areas 6 . There are several cited reasons that could explain the lack of enthusiasm toward biosimilars, including the lack of provider confidence, uncertainty about substitution, and a lack of patient awareness and education 12…”
Section: Discussionmentioning
confidence: 99%
“…This would also provide major advantages for patients and communities such as that financial resources may be more efficiently allocated to other important uses, which makes more innovative therapies available to patients 5 . In addition to being a cost saving phenomenon, switching to biosimlars is something to be considered as a medical issue, particularly if it could occur with other medicines as well 6 …”
Section: Introductionmentioning
confidence: 99%
“…Observational studies of the use of epoetins and granulocyte colony-stimulating factors in patients with chronic kidney disease or cancer in Italy have demonstrated that there is frequent switching between different biological products belonging to the same class in routine clinical care [24,25]. Post-marketing studies conducted in population-based databases have provided additional evidence of the comparative effectiveness and safety of originator and biosimilar epoetins, and have shown that switching from originator epoetin to a biosimilar epoetin, or vice versa, is safe and effective [26][27][28].…”
Section: Current Evidence On the Effects Of Switchingmentioning
confidence: 99%